Reticulum Traumatic Pericarditis (Research, Society and Development, 2024)
Traumatic reticulopericarditis typically arises from injury and perforation of the reticulum caused by the ingestion of foreign objects. These objects may be present in the animal's feed and can detach from tractor tires or from the coverings used for silage. This condition can inflict significant damage on the animal, potentially leading to various other infections and diseases, resulting in economic losses for the owners. This report aims to present a case of traumatic reticulopericarditis. Given the progression of the illness, the treatment administered was ineffective, and the animal was euthanized. The subsequent necropsy provided a definitive diagnosis, revealing macroscopic changes and a sharp object in the heart, indicative of traumatic reticulopericarditis. Due to its challenging nature to diagnose, this pathology is often only recognized when the animal is in an advanced stage of symptoms, with necropsy being the most common method for confirmation. It is crucial for professionals to share their experiences regarding this issue to foster advancements in evidence production and to disseminate preventive measures that enhance management practices and reduce the incidence of the disease.